Night wherever we go : a novel - Peyton, Tracey Rose (Ecco, an imprint of HarperCollins Publishers, 2023)
A gripping, radically intimate debut novel about a group of enslaved women staging a covert rebellion against their owners. On a struggling Texas plantation, six enslaved women slip from their sleeping quarters and gather in the woods under the cover of night. The Lucys--as they call the plantation owners, after Lucifer himself--have decided to turn around the farm's bleak financial prospects by making the women bear children. They have hired a "stockman" to impregnate them. But the women are determined to protect themselves. Now each of the six faces a choice. Nan, the doctoring woman, has brought a sack of cotton root clippings that can stave off children when chewed daily. If they all take part, the Lucys may give up and send the stockman away. But a pregnancy for any of them will only encourage the Lucys further. And should their plan be discovered, the consequences will be severe. Visceral and arresting, Night Wherever We Go illuminates each woman's individual trials and desires while painting a subversive portrait of collective defiance. Unflinching in her portrayal of America's gravest injustices, while also deeply attentive to the transcendence, love, and solidarity of women whose interior lives have been underexplored, Tracey Rose Peyton creates a story of unforgettable power.